2001
DOI: 10.1051/0004-6361:20010279
|View full text |Cite
|
Sign up to set email alerts
|

SCIDAR measurements at Pic du Midi

Abstract: We present SCIDAR measurements made at the Pic du Midi Observatory with PISCO. A series of vertical profiles of the refractive-index structure constant C 2 N (h) was obtained with the observations of the binary stars γ Del and γ Ari, with 30 second time sampling. In the free atmosphere, the turbulence was dominated by the contribution of a few well-separated atmospheric layers at altitudes in the range 8-20 km, with significant changes within a few minutes. We describe a new method based on the CLEAN algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 19 publications
2
58
0
Order By: Relevance
“…We note that the differences in vertical C 2 N structure are observed, at least in the 21/22 night, near the ground and in the higher part of the atmosphere. Beside this, it has been shown that the statistical noise, that intrinsically affects the GS measurements, increases near the ground and in the high part of the atmosphere (Vernin & Azouit 1983;Tokovinin 1997;Prieur et al 2001). Therefore we performed a deeper study to confirm that the seeing variations estimated in our study are effectively due to a real different distribution of the turbulence and not to some noise.…”
Section: Experimental Validationsupporting
confidence: 65%
“…We note that the differences in vertical C 2 N structure are observed, at least in the 21/22 night, near the ground and in the higher part of the atmosphere. Beside this, it has been shown that the statistical noise, that intrinsically affects the GS measurements, increases near the ground and in the high part of the atmosphere (Vernin & Azouit 1983;Tokovinin 1997;Prieur et al 2001). Therefore we performed a deeper study to confirm that the seeing variations estimated in our study are effectively due to a real different distribution of the turbulence and not to some noise.…”
Section: Experimental Validationsupporting
confidence: 65%
“…The SCIDAR technique has been the subject of many papers (e.g., Rocca et al 1974;Vernin & Azouit 1983;Caccia et al 1987;Avila et al 1997;Klückers et al 1998;Prieur et al 2001). Here we present only the guidelines of the method in order to introduce the quantities that are useful for this paper.…”
Section: The Scidar Methodsmentioning
confidence: 99%
“…We have chosen to use an iterative approach based on the CLEAN algorithm, as we did for the inversion of profiles 2 C N for SCIDAR measurements (Prieur et al 2001). We wanted to take advantage of the experience acquired working with the interactive program developed by Avila et al (2001), which had a demonstrated efficiency in providing good measurements.…”
Section: Principle Of Our Methodsmentioning
confidence: 99%
See 2 more Smart Citations